Padrão temporal e a influência das condições climáticas e ambientais nas fatalidades de quirópteros em um complexo eólico no sul do Brasil - Amaral, Izidoro Sarmento do (Universidade do Vale do Rio dos Sinos, 2019)
In Brazil, the energy demand created by economic development has rapidly and intensely transformed the natural landscape, not only with wind energy but also with other types of projects. These changes in an environment that has a mega diversity must be accompanied by studies that describe and can predict the effects of these changes on ecosystems, supporting efforts to reduce impacts and conserve the species. The relationship between bats and wind farms in Brazil is little known, and existing publications have been published in the last five years. In this context, in order to analyze the relationship between bat fatalities at the Santa Vitória do Palmar Wind Complex and their spatial and temporal patterns, between July 2014 and June 2018, monthly circular transects were carried out in search of carcasses in the around 129 wind towers. During the searches, the fatalities found were recorded along with the tower number, date and distance of each carcass found to the base of the tower. All carcasses found were identified at the lowest possible taxonomic level and were later removed to avoid recounts. Information on deaths was first analyzed in annual sets, using the Friedman test and then separated by seasons to understand the influence of different land use classes on the spatial pattern observed in fatalities. To investigate the relationship of activity indices with climate, acoustic monitoring of the bat community was used to generate generalized linear models (GLM) with Poisson distribution, using climate variables as predictor variables. The second order Akaike Information Criterion (AICc) and the coefficient of determination (R2) were used to rank and select the models, comparing models with all possible combinations of predictor variables. At the end of 48 months, 266 bat carcasses belonging to six species of insectivorous bats were recorded. The results showed the predominance of the species Tadarida brasiliensis among the observed fatalities, in addition to the first record of death of specimens of the genus Eptesicus in wind towers. The data also revealed that deaths occur exclusively between the months of October and May and that the wind towers closer to the urban center concentrated a greater number of deaths. The time series of bat deaths revealed a higher frequency of deaths in the first year (69% in 2014), followed by a reduction in the next two years and a small increase in the fourth year of monitoring. The models curiously revealed a positive relationship between activity and wind speed. According to the data obtained, the best possible scenarios for the installation of new parks would be places with a distance greater than 4 km from urbanized centers and with a predominance of fields. Thus, the most important mitigation proposal for bat deaths in the study region is the programming of the towers to stop on nights with certain weather conditions, which should be based on minimum criteria such as the ideal temperature range for the activity ( 15°C – 22°C) where 83% of the activity occurs and the seasonal distribution of deaths, applying the measures mainly in the most critical months, between December and March.
Keywords: Monitoramento ambiental; Mitigação; Morcegos; Environmental monitoring; Mitigation; Bats; ACCNPQ::Ciências Biológicas::Biologia Geral